Microwave Plasma Enhancing Mg-Based Hydrogen Storage: Thermodynamics Evaluation and Economic Analysis of Coupling SOFC for Heat and Power Generation - Wang, Huan; Yan, Hongli; Ren, Jianwei; Li, Bo; Nyallang Nyamsi, Serge; Wu, Zhen (Frontiers in Thermal Engineering, 2022)
Hydrogen, as a kind of green and efficient energy, plays an increasingly important role in current social development. Hydrogen storage technology is considered to be one of the main bottlenecks of limiting the large-scale application of hydrogen energy. The solid-state hydrogen storage technology based on Mg-based materials has received extensive attention due to its advantages of high hydrogen capacity, good reversibility, and low cost, but there are still shortcomings such as high reaction temperature, large energy consumption and slow reaction kinetics. In order to solve these problems, this paper proposes a new method of using microwave plasma to ionize hydrogen into H- ion. The possible activation mechanism of microwave plasma to improve the hydrogen storage properties is put forward. Based on the activation mechanism, the thermodynamic performance of Mg-based hydrogen storage is evaluated using density functional theory. It is concluded that the reaction temperature is significantly reduced from 339 ℃ to 109 ℃ with the help of microwave plasma. In addition, the comparison between conventional heating hydrogen storage process based on MgH2 and microwave enhanced advanced hydrogen storage process based on MgH2 systems coupled with solid oxide fuel cells for heat and power generation is conducted to evaluate the economic feasibility. The results show that the energy consumption cost of the proposed microwave plasma enhancing hydrogen storage system is approximately 1.71 /kgH2, which is about 50% of the energy consumption cost of conventional system.